THE EFFECTIVENESS OF USING ILLUSTRATED FOLKTALE â€œTHE PRINCESS FARMERâ€ TO TEACH READING COMPREHENSION OF NARRATIVE TEXT A Quasi Experimental Research at the Tenth Year Students of SMK Diponegoro Juwana in the Academic Year of 2015/2016 (ELT Forum: Journal of English Language Teaching, 2016)
This article is about the use of illustrated folktale â€œThe Princess Farmerâ€ as a strategy to develop the studentsâ€™ reading comprehension. In order to achieve the objectives of this research, the writer adopted a quasi-experimental research design. The subjects of this research were class X-AK 1 and X-AK 2 of SMK Diponegoro Juwana, in the academic year of 2015/2016 which consisted of 20 students in each class. In this study X-AK 2 was selected as the control group and X-AK 1 was selected as the experimental group. There were 5 meetings in this study. In the first meeting, there was pre-test, in the second, third, and fourth meetings there were treatments, and in the fifth meeting there was post-test. In order to collect data about studentsâ€™ reading comprehension of narrative text, the writer used pre-test and post-test to know the studentsâ€™ differences. Besides used test, this study also used questionnaire.Â  The result of this study showed that the use of illustrated folktale â€œThe Princess Farmerâ€ can measure studentsâ€™ reading comprehension of narrative text well. Based on the result of this study, the writer concluded that the use of illustrated folktale â€œThe Princess Farmerâ€ gave a good contribution in English teaching and learning, especially in the area reading comprehension of narrative text.